Protein expression of TGF-β, SMAD2 and RUNX3 in normal stomach, chronic gastritis and gastric adenocarcinoma - Ismail, Ahmad Zharif (2016)
Though recorded as 7th most common type of cancer worldwide, gastric cancer ranked 2nd for the highest mortality rate for cancer related cases. With medical evidences that supported higher curability chances should tumor were detected in earlier initial stages, current medical technology development to facilitate early detection of gastric cancer remain infeasible and costly. Thus discovery of biomarker that is concurrently altered from normal physiological condition in tumor progression would be an ideal solution to address the problem. This study focuses on controversial pleiotropic protein expression, TGF-β and its downstream associated products Smad2 and RUNX3 in samples that represent stages of multistep tumorigenesis. A total of 162 tissue samples in the form of formalin fixed paraffin embedded (FFPE) were employed. Out of these, 57 were screened negative for any pathological symptoms (normal), 23 Helicobacter pylori associated chronic gastritis, 42 non Helicobacter pylori chronic gastritis and 40 gastric adenocarcinoma tissues. Through semiquantitative score immunostaining, decreasing percentage of TGF-β1 immunostaining positive were detected from normal (49.1%) to chronic gastritis (24.6%) and adenocarcinoma (17.5%) samples. These alterations were proven to be statistically significant with p values less than 0.05 at every successive stages.SMAD2 however expressed inverse relation in which samples with strongly positive immunostain increases from 5.3% in normal to 7.7% in chronic gastritis and 16.2% in gastric adenocarcinoma. In spite of these increment, unlike samples stain for TGF-β, only one pair of group (normal, chronic gastritis) showed significant increment for 2 paired Mann Whitney test. In addition, no correlation of TGF-β- SMAD2 expression tested in the same samples were found using Spearmann correlation test. For RUNX3 we report negative expression on all types of gastric tissues amidst some positive lymphocytes stain present in certain number of samples. For these significant changes of TGF-β and SMAD2 expression from normal gastric to inflamed conditions, we report that these proteins could become potential inflammatory biomarkers in conclusion to this study.